2012
DOI: 10.3329/bjvm.v8i2.11198
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Prevalence of Brucellosis in Black Bengal Goats in Bangladesh

Abstract: A total of 242 milk and 208 blood samples of goat were collected from three organized goat farms and surrounding rural areas of Bangladesh Agricultural University to determine the prevalence and associated risk factors of brucellosis in Black Bengal goats during the period from December 2008 to September 2009. Milk samples were screened by Milk Ring Test (MRT) and serum samples by Rose Bengal test (RBT) and Micro Agglutination Test (MAT) for detection of brucella specific antibody in milk and blood respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
6
11
1
Order By: Relevance
“…A higher seroprevalence in female sheep and goats has been reported from the district of Peshawar, Pakistan [22], whereas higher seropositivity in male sheep and goats has been reported in goats in Bangladesh and Mexico [23,24]. In the present study, the number of male animals was lower than the number of female animals because female animals were served by positive rams of the same herd or were of older age, increasing the risk of getting infected.…”
Section: Discussioncontrasting
confidence: 54%
“…A higher seroprevalence in female sheep and goats has been reported from the district of Peshawar, Pakistan [22], whereas higher seropositivity in male sheep and goats has been reported in goats in Bangladesh and Mexico [23,24]. In the present study, the number of male animals was lower than the number of female animals because female animals were served by positive rams of the same herd or were of older age, increasing the risk of getting infected.…”
Section: Discussioncontrasting
confidence: 54%
“…This result supports the findings of Islam et al (2010). The present study reported higher prevalence of brucellosis in case of female sheep and goats than male but the difference was not statistically significant (p > 0.05).…”
Section: Discussionsupporting
confidence: 90%
“…A study conducted at Gaibandha district of Bangladesh reported 3.39% prevalence of brucellosis in sheep (Rahman et al, 2012). Islam et al (2010) recorded 3.85% prevalence of brucellosis in black Bengal goat on the farms located at Savar and Rajshahi in Bangladesh. A study conducted in Saudi Arabia reported 11.6% prevalence of brucellosis in small ruminants (Radwan et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher incidence of the disease was observed in goats with reproductive disorders (Rahman et al, 1988). Overall prevalence of brucellosis in goats were 1.7% in Mymensingh and Dhaka districts, 0% in Dhaka and Lalmonirhat districts, 3.9% in Mymensingh district, 5.8% in Bogra and Mymensingh districts, 6.7% in Bagherhat districts, 0% in Bogra district, 4% in Gaibandha district and 2.9% in Sirajgonj district (Uddin et al, 2007a, b;Das et al, 2008;Islam et al, 2010;Rahman et al, 2011bRahman et al, , 2012b. Potential risk factors for brucellosis in goats included age, sex, pregnancy status, management system (concrete floor versus mud floor; flock rearing vs. individual rearing; non grazing versus free grazing; mixed with cattle versus without cattle; and rural versus farm goats) and reproductive disorders (abortion vs. retained placenta).…”
Section: Brucellosis In Goatmentioning
confidence: 99%